Ceftriaxone reduces L‐dopa–induced dyskinesia severity in 6‐hydroxydopamine parkinson's disease model. Issue 11 (20th June 2017) - Chotibut, Tanya; Meadows, Samantha; Kasanga, Ella A.; McInnis, Tamara; Cantu, Mark A.; Bishop, Christopher; Salvatore, Michael F.
ABSTRACT: Background: Increased extracellular glutamate may contribute tol ‐dopa induced dyskinesia, a debilitating side effect faced by Parkinson's disease patients 5 to 10 years afterl ‐dopa treatment. Therapeutic strategies targeting postsynaptic glutamate receptors to mitigate dyskinesia may have limited success because of significant side effects. Increasing glutamate uptake may be another approach to attenuate excess glutamatergic neurotransmission to mitigate dyskinesia severity or prolong the time prior to onset. Initiation of a ceftriaxone regimen at the time of nigrostriatal lesion can attenuate tyrosine hydroxylase loss in conjunction with increased glutamate uptake and glutamate transporter GLT‐1 expression in a rat 6‐hydroxydopamine model. In this article, we examined if a ceftriaxone regimen initiated 1 week after nigrostriatal lesion, but prior tol ‐dopa, could reducel ‐dopa–induced dyskinesia in an established dyskinesia model. Methods: Ceftriaxone (200 mg/kg, intraperitoneal, once daily, 7 consecutive days) was initiated 7 days post‐6‐hydroxydopamine lesion (days 7‐13) and continued every other week (days 21‐27, 35‐39) until the end of the study (day 39 postlesion, 20 days ofl ‐dopa). Results: Ceftriaxone significantly reduced abnormal involuntary movements at 5 time points examined during chronicl ‐dopa treatment. Partial recovery of motor impairment from nigrostriatal lesion byl ‐dopa was unaffected by ceftriaxone. The ceftriaxone‐treatedl ‐dopa group had significantly increased striatal GLT‐1 expression and glutamate uptake. Striatal tyrosine hydroxylase loss in this group was not significantly different when compared with thel ‐dopa alone group. Conclusions: Initiation of ceftriaxone after nigrostriatal lesion, but prior to and duringl ‐dopa, may reduce dyskinesia severity without affectingl ‐dopa efficacy or the reduction of striatal tyrosine hydroxylase loss. © 2017 International Parkinson and Movement Disorder Society